Implementasi Pendidikan Karakter Di Sekolah - Akidah, Sri (Al-Riwayah : Jurnal Kependidikan, 2022)
Character education in schools began to be applied in 2010 at the level of early education/kindergarten, elementary, junior high, high school, and college by incorporating the values of character in the learning of each subject. The values of these characters include religious, honest, responsible, healthy lifestyle, discipline, hard work, confident, entrepreneurial, creative, independent, curious, love science, aware of the rights and duties of others, obey the rules social, respectful work and achievements of others, polite, democratic, social and environmental, nationalist, and respect diversity. Impelementation of character education in schools is done through the preparation, implementation and assessment phase